Data collection tool for the follow-up survey targeting farmers in Egypt - Yigezu, Yigezu; Bikara, Innocent; Dessalegn, Bezaiet; Kasem, Eman (2023)
The data collection tools was developed to collect follow-up data among farmers that participated in the iNASHR project in Egypt